New series of a-resolvable and almost α-resolvable PBIB designs - Mohan R.N.; Kageyama, Sanpei (Utilitas Mathematica, 1997)
Taking the resolution sets of an affine α-resolvable (α ≥ 1) balanced incomplete block design a patterned method of construction of new series of α-resolvable two-associate group divisible partially balanced incomplete block (PBIB) designs and through a slightly different pattern of the resolution sets from the above, a construction of new series of almost α-resolvable PBIB designs are given.